Release of cell-free ice nuclei by Erwinia herbicola. - Phelps, P (1986)
Several ice-nucleating bacterial strains, including Erwinia herbicola, Pseudomonas fluorescens, and Pseudomonas syringae isolates, were examined for their ability to shed ice nuclei into the growth medium. Only E. herbicola isolates shed cell-free ice nuclei active at -2 to -10 degrees C. These cell-free nuclei exhibited a freezing spectrum similar to that of ice nuclei found on whole cells, both above and below -5 degrees C. Partially purified cell-free nuclei were examined by density gradient centrifugation, chemical and enzymatic probes, and electron microscopy. Ice-nucleating activity in these cell-free preparations was associated with outer membrane vesicles shed by cells and was sensitive to protein-modifying reagents.